"We also can. We're not worse": The Anglophone Wave in Russian indie music (Indi), 2008–2012. Issue 2 (May 2020) - Biasioli, Marco
Abstract: This article analyses the main cultural and political factors that contributed to the emergence of local Anglophone music in Russia between 2008 and 2012. While Russian indie groups had extensively sung in English before (with scarce public recognition), a conjunction of circumstances encouraged the appearance of a conspicuous Russian Anglophone music scene in the Medvedev years. These were a perceived political relaxation, internally and in East–West relations; Russian economic growth and the subsequent renovation of Moscow; and the connectivity and expansion of the independent music community. The article also argues that the success of local Anglophone bands, as well as the appearance of an 'indie' sound and an 'indie' music scene ( indi ), was the result of a concerted effort by Russian music participants to bring and incorporate the Other – the West – into Russia's everyday life. The English language, correspondingly, functioned as a 'tool' for this operation.